Comparison of the Efficacy of Hydrogen Peroxide and Salt for Control of Fungal Infections on Brown Trout (Salmo trutta) Eggs - Novakov, Nikolina; Mandić, Vladislav; Kartalović, Brankica; Vidović, Bojana; Stojanac, Nenad; Kovačević, Zorana; Plavša, Nada (Acta Scientiae Veterinariae, 2018)
Background: Fungal infections can cause serious problems infecting fish eggs, especially unfertilized or dead eggs. In the past, this problem was solved by using very effective chemicals such as malachite green and formalin. But, due to its toxicity and carcinogenicity, malachite green was banned for use in fish intended for human consumption. Formalin also has been banned in most countries. Chemicals and drugs recommended for use to treat fungal infections are hydrogen peroxide, salt, potassium permanganate etc. The goal of the present study was to determine and compare the efficacy of antifungal effects of hydrogen peroxide and sodium chloride on brown trout eggs. Materials, Methods & Results: The experiment was conducted in the brown trout hatchery, Šipovo, Bosnia and Herzegovina. The experimental groups contained 500 and 1000 mg/L of hydrogen peroxide with 15 and 30 min of exposition; 1 and 2.5% of sodium chloride with 15 and 30 min of exposition and a negative control group (no chemical treatment). The treatment concentrations were calculated and prepared from hydrogen peroxide of 35% active ingredient, and sodium chloride (sterilized) of 100% active ingredient. Eggs for the study were spawned from 11 females and 4 males. The first treatment was performed on the fourth day, and each next treatment was performed at 3-day intervals. Six treatments were administered until the 19th day after the fertilization. The treatment of the eggs was provided until the eggs reached the eyed stage. The effectiveness of the chemical treatments was measured by a hatch rate. There was a significant difference between all treated groups and the negative control group (P < 0.05). Hydrogen peroxide with a concentration of 500 mg/L for 30 min was the most effective and demonstrated a higher hatching rate (75.7%). Sodium chloride treatments resulted in statistically significantly lower hatching rates than hydrogen peroxide treatments. The hatching rate in salt treatment with a concentration of 2.5% for 30 min was 27.3% lower than in hydrogen peroxide treatment with a concentration of 500 mg/L for 30 min. Discussion: Hydrogen peroxide is an effective antifungal, antibacterial and antiviral compound, and according to the Food and Drug Administration (FDA), hydrogen peroxide and salt are approved and classified as a low regulatory priority for the control of oomycetes on all species and life stages of fish. It is considered to be a very environmentally compatible chemical because it does not produce any toxic bioproducts when it decomposes. Hydrogen peroxide stood out as the best candidate substance for fungal control. The fact that the treatment with hydrogen peroxide at a concentration of 500 mg/L for 30 min was more effective than treatments at a concentration of 1000 mg/L can be explained by temperature dependency and treatment frequency of this chemical. Salt was not such an effective fungicide as hydrogen peroxide. When using salt, toxicity to the eggs should also be considered. Salt solutions may cause egg deaths at levels of 2.5% or higher. It is possible that high salinities have an inhibitory effect on the movement of fish embryo due to the high osmotic impact on the perivitelline layer. Thus, hydrogen peroxide has proven to be efficient, inexpensive, easy to use and environmentally safe in preventing fungal infections on brown trout eggs.